About the Author - Yulia N. Grekova; Muza M. Kokhan; Igor A. Kuklin; Nina P. Toropova (LLC "MEDIAFORMAT", 2022)
Extramammary Paget's disease (EMPD) is a rare variant of adenocarcinoma, the most common localization of which is a vulva. Clinical manifestations are nonspecific and can be initially diagnosed as manifestations of other dermatoses, which makes early diagnosis difficult. The most effective diagnostic method is a pathomorphological and immunohistochemical examination of the skin biopsy. We present a clinical case of EMPD in a 42-year-old HIV-infected female patient.